"Balancing Field-General and Subfield-Specific Contributions When Addressing, Utilizing, or Assessing a Theory's Explanatory Power". Issue 4 (8th August 2022) - Holbert, R. Lance; Baik, Elizabeth S.; Tallapragada, Meghnaa; Tolan, Colleen M.; LaMarre, Heather L.; Hardy, Bruce W.
ABSTRACT: Explanatory power is a key criterion for assessing the strength of a theory. This essay provides an expanded detailing of explanatory power's three components: Plausibility, range, and postdiction. In addition, a case is made for how plausibility advancements signal field-general contributions, range-based works gravitate toward subfield-specific offerings, and postdiction assessments can be field-general or subfield-specific. This discussion is grounded with a focus on four theories: Agenda Setting, Cultivation, Uses and Gratifications, and Social Cognitive Theory. Implications for future theory advancement are discussed and short- and long-term research initiatives are detailed.